1994
DOI: 10.1083/jcb.125.5.989
|View full text |Cite
|
Sign up to set email alerts
|

A novel cochaperonin that modulates the ATPase activity of cytoplasmic chaperonin.

Abstract: Abstract. The folding of or-and/3-tubulin requires three proteins: the heteromeric TCP-l-containing cytoplasmic chaperonin and two additional protein cofactors (A and B). We show that these cofactors participate in the folding process and do not merely trigger release, since in the presence of Mg-ATP alone, u-and B-tubulin target proteins are discharged from cytoplasmic chaperonin in a nonnative form. Like the prokaryotic cochaperonin GroES, which interacts with the prototypical Escherichia coli chaperonin Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
68
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 43 publications
4
68
1
Order By: Relevance
“…Although averaged images of the particle with and without bound substrate have been presented (Marco et al, 1994), detailed information about the structural and biochemical properties of the eukaryotic chaperonin particle is still sparse. This may be due in part to the limitations of isolation procedures that rely on size fractionation, limited capacity affinity supports, and laborious folding assays (Frydman et al, 1992;Gao et al, 1992;Lewis et al, 1992).…”
mentioning
confidence: 99%
“…Although averaged images of the particle with and without bound substrate have been presented (Marco et al, 1994), detailed information about the structural and biochemical properties of the eukaryotic chaperonin particle is still sparse. This may be due in part to the limitations of isolation procedures that rely on size fractionation, limited capacity affinity supports, and laborious folding assays (Frydman et al, 1992;Gao et al, 1992;Lewis et al, 1992).…”
mentioning
confidence: 99%
“…Gao et al (1994) cloned the mouse p14 cDNA and found no significant homologies to other known genes. These authors have suggested that p14 is the CCT cochaperThe basic microtubule units are tubulin dimers which are formed from c1-and B-tubulin monomers.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas fully functional actin and ␥-tubulin polypeptides are released from the cytosolic chaperonin complex, ␣-tubulin and ␤-tubulin polypeptides are further processed by tubulin-folding cofactors (TFCs; for review, see Lewis et al 1997;Nogales 2000). TFCs were originally identified by their tubulin-folding activity in extracts from mammalian cells (Gao et al 1994;Llosa et al 1996;Melki et al 1996; Tian et al Cold Spring Harbor Laboratory Press on May 9, 2018 -Published by genesdev.cshlp.org Downloaded from …”
mentioning
confidence: 99%